Koncepcja opcji realnych w teorii i praktyce zarządzania przedsiębiorstwem - Sus-Januchowska, Aleksandra (Real Option Analysis - Theory and Practice, 2008)
The aim of this report is to present the real option analysis as an effective way of strategic management. The article concentrates on the role of real options in strategie risk factors and uncertainty; it defines real options, illustrates a different kind of real options and research in this subject. The last part shows that ROA could be a high-quality solution in current organizations, where everything changes in very high-speed way and unforeseeable, even as a way of thinking. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 24, s. 234-242